Agreement between spectral-domain and time-domain OCT for measuring RNFL thickness - Vizzeri, G; Weinreb, R N; Gonzalez-Garcia, A O; Bowd, C; Medeiros, F A; Sample, P A; Zangwill, L M (British journal of ophthalmology, 2009)
Background/aims:To evaluate spectral-domain (SD) optical coherence tomography (OCT) reproducibility and assess the agreement between SD-OCT and Time-Domain (TD) OCT retinal nerve fibre layer (RNFL) measurements.Methods:Three Cirrus-SD-OCT scans and one Stratus-TD-OCT scan were obtained from Diagnostic Innovations in Glaucoma Study (DIGS) healthy participants and glaucoma patients on the same day. Repeatability was evaluated using Sw (within-subject standard deviation), CV (coefficient of variation) and ICC (intraclass correlation coefficient). Agreement was assessed using correlation and Bland–Altman plots.Results:16 healthy participants (32 eyes) and 39 patients (78 eyes) were included. SD-OCT reproducibility was excellent in both groups. The CV and ICC for Average RNFL thickness were 1.5% and 0.96, respectively, in healthy eyes and 1.6% and 0.98, respectively, in patient eyes. Correlations between RNFL parameters were strong, particularly for average RNFL thickness (R2 = 0.92 in patient eyes). Bland–Altman plots showed good agreement between instruments, with better agreement for average RNFL thickness than for sectoral RNFL parameters (for example, at 90 µm average RNFL thickness, 95% limits of agreement were −13.1 to 0.9 for healthy eyes and −16.2 to −0.3 µm for patient eyes).Conclusions:SD-OCT measurements were highly repeatable in healthy and patient eyes. Although the agreement between instruments was good, TD-OCT provided thicker RNFL measurements than SD-OCT. Measurements with these instruments should not be considered interchangeable.